Kimura Lymphadenitis of the Retroauricular Region in a 48-Year-Old Indonesian Male: A Rare Case Report with Long-Standing Disease Duration - Kadek Susi Setyawati; Ketut Suardamana; Dekta Filantropi Esa (Phlox Institute: Indonesian Medical Research Organization, 2026)
Introduction: Kimura disease is a rare chronic inflammatory disorder of unknown etiology predominantly affecting young Asian males, characterized by painless subcutaneous masses in the head and neck region, peripheral eosinophilia, and elevated serum immunoglobulin E levels. This condition remains underreported in Southeast Asian countries, particularly Indonesia, leading to significant diagnostic delays. Case presentation: We present the case of a 48-year-old Indonesian male from Bali who presented with a retroauricular mass persisting for 10 years prior to definitive diagnosis. The patient had undergone surgical excision one month prior and was subsequently referred for further evaluation. Laboratory investigations demonstrated leukocytosis with a white blood cell count of 13.82 × 103/µL, peripheral eosinophilia of 8.60%, absolute eosinophil count of 1.19 × 103/µL, and elevated total serum immunoglobulin E of 168.16 KUI/L. Renal function was preserved without proteinuria despite prolonged disease duration. Histopathological examination confirmed Kimura lymphadenitis with reactive follicular hyperplasia, dense eosinophilic microabscesses, vascular hyalinization, and multinucleated Warthin-Finkeldey giant cells. The patient was managed with surgical excision followed by oral methylprednisolone 8 mg daily with planned tapering. Conclusion: This case highlights diagnostic challenges of Kimura disease in Indonesian clinical settings and the importance of histopathological confirmation.